(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2024)
The main source of human exposure to heavy metals is through food, as they tend to accumulate in some plants and fruits through the trophic chains. The objective of the research was to determine the presence of cadmium in fermented and dried fruits of the Santander variety Colombia The research aimed to determine the presence of cadmium in cocoa beans. The samples were collected at the SENA agricultural centre and analysed at the food quality control laboratory of the University of Pamplona, using atomic absorption spectroscopy. The concentration of Cd was determined by performing a calibration curve from a certified Cadmium standard at a specific wavelength of 288.8 nm in a SHIMADZU AA 7000 Atomic Absorption Spectrophotometer with air-acetylene flame, taking into account the necessary characteristics to avoid interferences, achieving an accurate analysis. According to the European Food Safety Authority, the dietary exposure to cadmium in European countries is close to or slightly above the acceptable weekly intake of 2.5 ug/kg body weight. Given the high content of heavy metals, including cadmium, in cocoa, its demand in national and international markets is limited. The results indicated that cadmium was not detected in the sample analysed